Media and social representations: sociocultural and environmental impacts of the Brazil / Argentina integration bridge - Pinto, Muriel; Almeida, Cristóvão Domingos de (Revista Hipótese, 2018)
The objective is to analyze the socio-cultural relations of the border, São Borja- Brazil / São Tomé-Argentina. The boundary is marked by the boundary of the Uruguay River, with importance for the communication processes, the commercial relations and the actions of the riverside ones in the contemporaneity. We base the study on the concepts of media, memory, social representations, socio-territorial identities and on the interpretation of political articulations during the period of construction of the integration bridge. Methodologically, we used the documentary research and survey of the reports on the construction of the Integration Bridge to understand from a content analysis the regional historiography and the socio-cultural practices of the border. We infer that the frontier is a porous and also selective region, characterized by a border identity marked by missionary, gaucho and riverside cultural interactions. We conclude that the impacts of the construction of the bridge generate concern on the part of the popular ones with a probable extinction of traditional ways of life.
Keywords: Media; Border; Representations; Identities